Aspek Dasar Penggunaan CT Scan dalam Kedokteran - Suroyo Suroyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
CT scan is a reconstruction of tomographic slices of objects by a computer. The first application in the clinic was done in 1967 by the efforts of Godfrey Mounsfield in the Central Research Laboratory of EMI Ltd. in England. Its superiority compared with conventional tomography lies in the high power of resolution and its ability to distinguish soft tissues with 0.5% of the emission difference of X-ray, while with the conventional tomography the emission difference must be more than 5%. CT scan is very useful in both diagnostics and radiation therapy. Key Words: CT scan — conventional tomography — resolution power — radiation therapy —X-ray